2018
DOI: 10.21815/jde.018.038
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Basic and Clinical Sciences: Faculty Perspectives at a U.S. Dental School

Abstract: Although dental education has traditionally been organized into basic sciences education (first and second years) and clinical education (third and fourth years), there has been growing interest in ways to better integrate the two to more effectively educate students and prepare them for practice. Since 2012, The University of Texas School of Dentistry at Houston (UTSD) has made it a priority to improve integration of basic and clinical sciences, with a focus to this point on integrating the basic sciences. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Clinical experts due to busy hospital routine cannot justify their roles as teachers in preclinical integrated modules. 13 Scant literature is available on the use of Near-Peer tutors in SGDs, along with faculty, to deliver correlational concepts, in an integrated curriculum in preclinical years. Our study aims to generate qualitative data on the perceptions of Near-Peer tutors about NPAL and, their gains after tutoring small groups to deliver complex integrated concepts.…”
mentioning
confidence: 99%
“…Clinical experts due to busy hospital routine cannot justify their roles as teachers in preclinical integrated modules. 13 Scant literature is available on the use of Near-Peer tutors in SGDs, along with faculty, to deliver correlational concepts, in an integrated curriculum in preclinical years. Our study aims to generate qualitative data on the perceptions of Near-Peer tutors about NPAL and, their gains after tutoring small groups to deliver complex integrated concepts.…”
mentioning
confidence: 99%
“…24 A recent study at the University of Texas School of Dentistry at Houston found that both clinical and basic science faculty members valued the importance of integration of basic sciences into the clinical curriculum, but the basic scientists were more likely to integrate and collaborate than the clinicians. 25 In our study, most of the respondents recognized PM/PD as an important part of dental curricula and reported feeling that PM/PD should be taught in both the 2014 (77%) and 2017 (90%) surveys, with a slight upward trend indicating the need to educate students to be prepared for future advances after graduation. However, implementation of the concepts of PM/PD into both didactic and clinical curricula were lacking.…”
Section: Discussionmentioning
confidence: 62%
“…Simulation was demonstrated in a study where senior students authored case‐based small group sessions for first‐year students in biochemistry 12 . Another example of integration includes mandatory clinical rounds that teach basic science concepts along with the concepts of clinical courses 2 …”
Section: Discussionmentioning
confidence: 99%
“…However, faculty respondents of the present study shared mixed responses when asked if clinical shadowing is challenging. Other studies report challenges when it comes to certain topics such as anatomy and neurobiology 2 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation